Charcoal Rot of Strawberries Caused by Macrophomina phaseolina - Natalia A Peres; J. S. Baggio; J. C. Mertely (EDIS)
Charcoal rot is caused by Macrophomina phaseolina and has become more prevalent in Florida strawberry fields since methyl bromide was phased out. This 4-page publication describes the symptoms, development, and control of charcoal rot in strawberry fields. Written by N. A. Peres, J. S. Baggio, and J. C. Mertely and published by the UF/IFAS Department of Plant Pathology, February 2018. http://edis.ifas.ufl.edu/pp161